UPAYA PENINGKATAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN LAGU SEBAGAI MEDIA PEMBELAJARAN - Elvira Hoesain Radia (Universitas Sarjanawiyata Tamansiswa, 2018)
Abstract: It is undeniable that The success of a learning process can only be seen through student learning outcomes. Good learning outcomes are assumed to be the result of a good classroom learning process as well. The learning process will be success by the implementation of appropriate method or learning media. This study is a Classroom Action Research using Kemmis and Taggart Model. This study aims to improve the learning outcomes of grade 4 Elementary Students by using songs as a medium of learning. The results obtained that song is an effective learning media to be used in Social Study learning since it can help students in memorizing the learning materials as wells as carrying out active and fun learning.